“The Dream Team”: Using a Health Equity and Social Justice Lens to Define the “T” in CIT - Taylor, Sabrina (Criminal justice policy review, 2025)
In the continuing wake of a historic reform movement that began in 2020, Crisis Intervention Team (CIT) programs are enjoying a moment in the national spotlight. Much of this attention is negatively focused on police officers and the departments in which they serve. However, police represent just one of a trio of stakeholders commonly associated with CIT, including community advocacy groups and mental health providers. The negative attention can be frustrating for police and other criminal justice professionals because they have no direct control over health care and how it is provided. Indeed, even the local governments that oversee most of the criminal justice activity associated with CIT have little direct control over health care infrastructure. However, local governments do directly control much of the infrastructure that influences underlying conditions of health such as access to clean water, sanitation, education, housing, and employment. Health equity and social justice frameworks make clear that multiple sectors need to collaborate and strategically plan a multi-pronged approach to addressing health equity, including mental health. The Memphis Model of CIT implementation, when properly understood, can provide an effective roadmap grounded in health equity and social justice to enable local communities to address systemic challenges.